1999
DOI: 10.1021/jo980767y
|View full text |Cite
|
Sign up to set email alerts
|

Allylation of Imines with Allyltrimethylsilane and Experimental Evidences for a Fluoride-Triggered Autocatalysis Mechanism of the Sakurai−Hosomi Reaction

Abstract: This article reports the reaction of allyltrimethylsilane 1 with aldimines 2 in the presence of tetran-butylammonium fluoride to give the corresponding homoallylamines 3 in moderate to excellent yields. The allylation mechanism of imines as well as that of aldehydes can be reasonably interpreted by a fluoride-triggered autocatalytic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 36 publications
1
31
0
4
Order By: Relevance
“…Studies by Hou and co-workers have shown that the ammonium alkoxides such as 149 that are produced in allylations with allyltrimethylsilane and tris(dimethylamino)sulfonium difluorotrimethylsilicate (TASF) are in fact active catalysts for subsequent allylations (Scheme 51). [212] In addition, numerous examples of nucleophilic activation in the reaction of silyl nucleophiles with alkoxides exist, thus lending further support to the kinetic competence of this pathway. In-depth kinetic studies similar to those performed by Kuwajima and co-workers [211] are clearly warranted to establish the role of fluoride ions in the aldol and allylation reactions.…”
Section: Allylationmentioning
confidence: 97%
“…Studies by Hou and co-workers have shown that the ammonium alkoxides such as 149 that are produced in allylations with allyltrimethylsilane and tris(dimethylamino)sulfonium difluorotrimethylsilicate (TASF) are in fact active catalysts for subsequent allylations (Scheme 51). [212] In addition, numerous examples of nucleophilic activation in the reaction of silyl nucleophiles with alkoxides exist, thus lending further support to the kinetic competence of this pathway. In-depth kinetic studies similar to those performed by Kuwajima and co-workers [211] are clearly warranted to establish the role of fluoride ions in the aldol and allylation reactions.…”
Section: Allylationmentioning
confidence: 97%
“…Nach Untersuchungen von Hou und Mitarbeitern sind Ammoniumalkoxide wie 149, die bei Allylierungen mit Allyltrimethylsilan und Tris(dimethylamino)sulfonium-difluorotrimethylsilicat (TASF) entstehen, tatsächlich aktive Katalysatoren für nachfolgende Allylierungen (Schema 51). [212] Darüber hinaus belegen viele Beispiele für die Aktivierung von Silylnucleophilen mit Alkoxiden, dass dieser Reaktionsweg möglich ist. Eingehende kinetische Studien ähnlich denen von Kuwajima [211] sind sicherlich wünschenswert, um die Aufgabe von Fluorid in den hier besprochenen Aldolreaktionen und Allylierungen zu bestimmen.…”
Section: Nucleophile Aktivierung Durch N-s*-wechselwirkungenunclassified
“…Das ändert jedoch nichts daran, dass die Nucleophilie in fluoridvermittelten Reaktionen auf die Wirkung einer LewisBase zurückzuführen ist. [212,213] 6.1. Die Beschleunigung von Aldolreaktionen durch Fluoridionen wurde einige Jahre später durch Heathcock und Mitarbeiter beschrieben.…”
Section: Nucleophile Aktivierung Durch N-s*-wechselwirkungenunclassified
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] As reported in the literature, allylic organometallics such as allylic Mg, [22,23] Zn, [24,25] In, [26][27][28][29] Sn, [30][31][32][33][34][35][36][37][38] Si, [39,40] B [25,41] and Sm [42,43] have been intensively investigated in allylation reactions. Among these organometallics, allylic stannanes have been widely used because of their easy availability, air and moisture stability, tolerance to functional groups and high selectivity.…”
Section: Introductionmentioning
confidence: 99%